NETWORK ANALYSIS ON YEAST COLONY SACCHAROMYCES CEREVISIAE GROWTH - Meiriska, Widya
Yeast colony growth which can grow and produce buds can be modelled by using circular granular cells in two-dimensional form. The organizations of particles in granular materials as modelled as yeast colony growth have complex organizations on a spatial scale. Such organizations may affect how materials respond or reconfigure when exposed to external interference or loading. Particles have been studied in theoretical and require the development and application of appropriate mathematical, statistical, physical and computational frameworks. Usually, granular materials have been explored using particles or circuit models that are implicit. Nowadays the development of network science has emerged as a powerful approach to investigate and characterize heterogeneous architecture in complex systems and diverse methods have yielded interesting insights into granular materials. In this study will learn granular materials (yeast colony growth) with the network-based approach and explore the potential of these frames to provide a useful description of yeast colony growth.